Reciprocal relations between recovery and work engagement: The moderating role of job stressors. - Sonnentag, Sabine; Mojza, Eva J.; Demerouti, Evangelia; Bakker, Arnold B. (Journal of Applied Psychology, 2012)
In this paper, we examined the within-person relations between morning recovery level (i.e., feeling refreshed and replenished) and work engagement throughout the day, and between work engagement throughout the day and the subsequent recovery level at the end of the workday. We hypothesized that job stressors (situational constraints, job demands) moderate these relations. A diary study over 1 workweek with 2 measurement occasions per day (N = 111 persons) provided support for most of the hypotheses: Morning recovery level predicted work engagement, and work engagement predicted subsequent recovery level at the end of the workday after controlling for morning recovery level. As predicted, situational constraints attenuated these relations, but job demands did not. The results suggest that recovery translates into employee work engagement, and work engagement, in turn, prevents a loss in recovery level throughout the day, particularly when situational constraints are low. Situational constraints seem to interrupt the reciprocal processes between recovery level and work engagement.